O espírito do capitalismo brasileiro retratado em conteúdos populares de gestão empresarial nas mídias digitais: modelos de empresa e formas de mobilização nos textos de influenciadores de LinkedIn - Duarte, Ricardo Mello (2020)
The aim of this study was to analyze how the spirit of capitalism shows itself in contemporary Brazil. In other words, we sought to observe how a set of reasons is provided to support and legitimize the engagement of certain actors - especially managers - in capitalist practices. Having the business management literature as a privileged receptacle of the spirit of capitalism, the research sought to look at the wide-ranging circulation of these contents through digital media. Thus, LinkedIn social network was used to gather texts published by “prominent users” and constitute a corpus of work. This set of texts, whose publication dates range from 2014 to 2019, was analyzed according to the capitalism legitimating dimensions proposed by Boltanski and Chiapello (2009). In order to elaborate an overview of how this literature treats the Brazilian company and its issues in the studied period, the research identified the main management problems addressed by the authors, as well as the solutions proposed in the texts to solve them and also the representations that are made about the previous forms of accumulation. Then, it was observed how these writings provide indications so that the engagement in capitalist practices can be seen through three dimensions: as a source of enthusiasm, as a provider of guarantees and as a contributor to a common good. In order to articulate these justifications, the spirit of capitalism necessarily makes references to recognized moral orders, which are analyzed through the economies of worth model (BOLTANSKI; THÉVENOT, 2006). Significant continuities were found with the panorama portrayed by international literature at the end of the last century. Regarding the dominant business models, there was a greater emphasis on seeking to overcome deliberate planning techniques; on risk as a way of stimulating learning; on the sharing economy; and on the search for purpose by workers and companies. The mobilizing dimensions of the spirit, which are no longer significantly influenced by the cité by projects, revealed great ideological heterogeneity and a remarkable rise in the influence of the inspired cité. The composite forms on which an important part of the reasons given are based suggest the formation of certain unstable compromises, exposing difficulties in generating a coherent order in the symbolic level. Thus, a scenario of ideological disarticulation is observed, which provides the basis for the reproduction of a complex or managerial mode of domination.